Criminal Law Politics: Corruption Eradication Strategy Through an Integrative Approach - Karlina Lina Apriani; Ahmad Raji Hidayat; Rato Eko Hendriyadi; Wahyu Hamdani; Surawijaya Surawijaya (Faculty of Law, University of Mataram, 2020)
The purpose of this research is to examine the politics of criminal law deeply in eradicating criminal law of corruption through an integrative approach. The method usingis normative legal research. Normative legal research methods or library research methods in legal research by reviewing existing legal materials. The integrative approach in overcoming corruption crime can be made integrally through two approaches, namely first, awareness between criminal politics and social politics directed to achieve particular objectives of the socio-political policies that have been set in order to achieve social welfare. Second, integration of efforts to tackle crime with penal and non-penal approach due to the reality of national law and the political facts of international law for enforcement on a national, regional, and global scale.